The Influence of Physical Environmental Conditions and Maternal Practices on Acute Respiratory Infections in Toddlers: Evidence from Lailangga Community Health Center, Indonesia - Hamlia Kasmadi; Ramadhan Tosepu; Yasnani (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Acute Respiratory Tract Infection (ARI), or Infeksi Saluran Pernapasan Akut (ISPA), remains one of the primary causes of morbidity and mortality among children under five, particularly in developing countries. ARI is a common childhood infectious disease marked by the involvement of the respiratory tract, an acute clinical course, and the presence of infection. Its high incidence in toddlers is strongly associated with environmental exposures and behavioral factors, especially in resource-limited settings. Objective: This study aims to investigate the relationship between physical environmental factors and maternal behaviors with the incidence of ARI among toddlers in the service area of the Lailangga Health Center, Wadaga District, West Muna Regency, in 2023. Methods: This quantitative study applied a cross-sectional design. The population comprised 47 mothers with toddlers residing in the Lailangga Health Center catchment area. Data were collected through structured interviews and direct environmental observation. Analysis was conducted using univariate methods to describe respondent characteristics and bivariate methods to test the statistical associations between variables. Results: The study showed that over 64% of toddlers had inadequate intake of essential nutrients such as energy, protein, fat, and carbohydrates. While 54.9% of mothers had moderate to high educational attainment, 69.5% of households were categorized as having poor environmental conditions. Statistically significant relationships were identified between ARI and various factors, including nutritional intake (energy, protein, fat, carbohydrates), vitamin A, iron, zinc, maternal education (p=0.004), and environmental conditions (p=0.000). Conclusion: ARI incidence in toddlers was significantly linked to poor environmental quality and maternal behavior. Poor air circulation, limited ventilation, and lack of maternal awareness were major contributing factors. Interventions focusing on improving household environments and enhancing maternal health literacy are recommended to reduce ARI risk in this population. Keywords: Toddlers, Acute Respiratory Tract Infection (ARI), Air Pollution, Maternal Knowledge, Attitudes, Practices, Ventilation.